State of the Art of Audio- and Video-Based Solutions for AAL - Aleksic, Slavisa; Agius, Jean Calleja; Camilleri, Kenneth; Cartolovni, Anto; Climent-Peerez, Pau; Colantonio, Sara; Cristina, Stefania; Despotovic, Vladimir; Erakin, Ekrem; Florez-Revuelta, Francisco; Germanese, Danila; Grech, Nicole; et al. (My University, 2022)
The report illustrates the state of the art of the most successful AAL applications and functions based on audio and video data, namely (i) lifelogging and self-monitoring, (ii) remote monitoring of vital signs, (iii) emotional state recognition, (iv) food intake monitoring, activity and behaviour recognition, (v) activity and personal assistance, (vi) gesture recognition, (vii) fall detection and prevention, (viii) mobility assessment and frailty recognition, and (ix) cognitive and motor rehabilitation. For these application scenarios, the report illustrates the state of play in terms of scientific advances, available products and research project. The open challenges are also highlighted.
Keywords: Emotional and affective state recognition; Silver economy; Active and Assisted Living; AAL applications; Data sensing and processing; Computer Vision; Audio-signal processing; Social Robotics; Human-Computer Interaction; Artificial Intelligence; Lifelogging and selfmonitoring; Vital signs remote monitoring; Co-design; Cognitive and motor rehabilitation; Frailty recognition; Mobility assessment; Fall detection and prevention; Gesture recognition; Activity and personal assistance; Activity and behaviour recognition; Food intake monitoring